Combination of acute exacerbation of idiopathic nonspecific interstitial pneumonia and pulmonary embolism after booster anti-COVID-19 vaccination. (2022) - Bocchino, Marialuisa; Rea, Gaetano; Buonocore, Anna; Lieto, Roberta; Mazzocca, Annalisa; Di Domenico, Arcangela; Stanziola, Anna A.
Abstract: Coronavirus disease-2019 (COVID-19) is a systemic disorder with the lung and the vasculature being the preferred targets. Patients with interstitial lung diseases represent a category at high risk of progression in the case of Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV)-2 infection, and as such deserve special attention. We first describe the combination of acute exacerbation and pulmonary embolism in an elderly ILD patient after booster anti-COVID-19 mRNA vaccination. Vaccines availability had significantly and safety impacted COVID-19 morbidity and mortality worldwide. Immunization against COVID-19 is indisputable but must not be separated from the awareness of potential adverse effects in fragile patients.